Perbandingan Penggunaan Antipsikotik Atipikal Tunggal Dan Antipsikotik Atipikal Kombinasi Terhadap Kadar Ldl Pada Pasien Skizofrenia - Toniara, Safriwan; thristy, Isra; Nuralita, Nanda Sari (Buletin Farmatera, 2026)
Abstract: Schizophrenia is a collection of psychotic disorders with irregularities in the thought process, which have the feeling that they are controlled by external forces, delusions, perceptual disorders and abnormal effects integrated with real situations or reality. The use of antipsychotics in schizophrenic patients is the treatment of this disease, especially the most commonly used atypical antipsychotic users. This study aims to compare LDL (low-density lipoprotein) levels in schizophrenia patients who use single atypical antipsychotics and combination atypical antipsychotics at Madani Hospital Medan, North Sumatra. This type of research is descriptive analytical using  a cross-sectional  method that takes data on variable-free bound variables at one time, which is housed at the Upt Health Laboratory. North Sumatra Provincial Health Office. The results of the Independent T-Test of the use of single antipsychotics and a combination of atypical antipsychotics on LDL levels in schizophrenia patients were p=0.001 (P≤0.05). There was a significant difference between the administration of a single atypical antipsychotic and a combination of atypical antipsychotics to LDL levels in patients with schizophrenia.